INVESTIGATION OF ACUTE TOXICITY OF PHORATE (AN ORGANOPHOSPHATE) ON FRESH WAETR FISH CYPRINUS CARPIO - DR. G. LAKSHMAIAH,; PROF. P. INDIRA, (International Journal of Pharma and Bio Sciences, 2014)
Acute toxicity of Phorate, a broad-spectrum organophosphorus insecticide for numerous crops throughout the world and potential toxic pollutant contaminating aquatic ecosystems, was investigated on the fingerlings of Cyprinus carpio using static bioassays over a period of 96 hours. The mortality rate of Cyprinus carpio was monitored under laboratory conditions for the period of 96 hrs. Bioassays were repeated three times and the data obtained was evaluated using Finney’s Probit Analysis Statistical Method. The 96 hours LC50 of the exposed fish to Phorate was determined to be 0.71 ppm/lit. The behavioural changes observed against Phorate intoxication were increased opercular movement, respiratory distress such as gasping for air, loss of equilibrium and erratic swimming prior to mortality. In the treated fishes significant change in the colour of the gills from dark red to brownish black, high mucus films over surface of gills was also observed.